Production of Polyhydroxybutyrate by Cupriavidus Necator CCGUG 52238 Using Organic Acids Recovered from Fermented Kitchen Waste - Omar, Farah Nadia (2011)
The amount of solid waste generated was gradually increased and currently in Malaysia, all the waste is disposed in the municipal landfill. Solid wastes generated aremainly characterized by high concentration of organic matter primarily from kitchen waste. In this study, the organic acids recovered from naturally fermented kitchen waste was utilized as a sole carbon source for the production of polyhydroxybutyrate (PHB). PHB production was achieved through two stage processes: organic acids recovered from naturally fermented kitchen wastes followed by PHB production utilizing the recovered organic acidsby Cupriavidusnecator CCGUG 52238 in batch and fed-batch mode of fermentation. Kitchen waste was fermented using 50 L bioreactor at 37°C with agitation of 150 - 200 rev/min. The initial pH of fermentation was adjusted to pH 7. After seven days ofkitchen waste fermentation, about 60 g/L of total organic acids could be produced where it comprised lactic acid (98%), acetic acid (1.8%) and formic acid (0.2%). Organic acids were recovered after undergo few treatment processes which were freezing and thawing, centrifugation, filtrationand evaporation methods. The effect of the treatments on the organic acids concentration, nitrogen content as well as total suspended solids (TSS) removal was also investigated. As a result, about 223.9 g/L of organic acids had been successfully recovered and concentrated from initial 25.7 g/L of total organic acids produced, 93% of TSS had been removed after filtration process and about 98% of total nitrogen content had reduced. This indicates that the stepwise recovery process was able to recover high concentration of organic acids as well as removes the suspended solids. The recovered organic acids from kitchen wastes were then utilized for PHB production by C. necator CCGUG 52238 in series of batch and fed batch experiments. In batch culture, fermentation was carried out in 2 L bioreactor and the pH and temperature was controlled at 7 and 30C, respectively. The dissolve oxygen level (DO) was maintained at 30%, via agitation 300-700 r/min. The maximum PHB content produced from kitchen wastes organic acids was 52.79% (w/w) withdry cell weight of 4.62 g/L. The PHB yield and productivitywere obtained at 0.382 g/g and 0.1091 g/L/h, respectively. In fed batch culture, experiment was conducted in 7 L of bioreactor with condition was set up as same as in batch fermentation. About five timesincrement in PHB production was achieved by applying feeding strategy for every 10 hours. The PHB yield and productivity obtained were 0.79 g/g and 0.49 g/L/h, respectively. Therefore, organic acids derived from kitchen waste have a potential to be used as one of a favorable substratefor PHB production by C.necator CCGUG 52238.